Influence of Specified vis-a-vis Commercial Mineral Mixture on Haemato-Biochemical Parameters and Serum Mineral Concentration in Crossbred Calves - Bhatt, Shriya; Mondal, Bidhan C; Palod, Jyoti; Kumar, Anil; Kumar, Ripusudan (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A study was conducted to discern the effects of supplementation of areas specific mineral mixture in comparison to commercial mineral  mixture on the haemato-biochemical and mineral profile of growing crossbred calves. Feeding trial was conducted for 120 days on 15  one-week-old calves that were randomly assigned to 3 equal groups, each of 5 heads. Group 1 received a basal diet (milk, calf starter,  green fodder as per NRC, 2001). Group 2 received a basal diet with commercial mineral mixture (Agrimin) supplementation, and Group  3 received a basal diet with areas specified mineral mixture (containing ionic mineral salts like dicalcium phosphate 99.40% and copper  sulphate 0.6%). All calves were fed whole milk, calf starter containing broken wheat, soyabean chura and deoiled rice bran, and green  fodder (berseem grass, oat and mustard). Milk was discontinued after 2 months. Blood samples were collected at the 1st, 8th, and  16th weeks of age of calves for haemato-biochermical analysis. Throughout the trial, there were no significant (p>0.05) differences in  haematological parameters. During 1st week, biochemical parameters did not differ significantly among the groups. At 8th week, group  3 showed a significant (p
Keywords: Crossbred calves; Haematology; Mineral; Serum biochemicals; Specified mineral